Correlates of MPOWER policies and tobacco smoking - an analysis of WHO South East Asia regional countries - Sudeep Kumar; Jagannath Purushotham (Tobacco Induced Diseases, 2018)
Background One of the greatest threat to global health is the epidemic of tobacco. One third of world's population use tobacco and almost half of whom die prematurely. The WHO Framework Convention on Tobacco Control (WHO FCTC) brought out MPOWER package of interventions country-level implementation of effective measures to reduce the tobacco demand.